Implementation of adaptive coding and modulation for satellite communication links in heavy rain region: an operators perspective - Abubakar, I. (Asian Research Publishing Network, 2016)
This contribution presents an implementation of adaptive modulation and coding (ACM) for the real operating satellite- based internet protocol (IP) communication system from the Nigeria communication satellite (NigComSat-1R) very small aperture terminal (VSAT) network. Specifically, different modulation schemes are chosen according to the weather conditions in order to achieve the highest available data rate and preserve the link availability. The experimental results indicate that at least a 24% bandwidth reduction can be achieved with the same data rate by implementing the ACM technique. Further work should focus on the ACM selection strategy based on the peculiarities of the meteorological characteristics in a specific area so that ACM implementation will lead to maximum efficiency in terms of radio resource management and exploitation.